Geotechnical aspects of alluvial soils at different depths under sodium chloride action in Najran region, Saudi Arabia: Field supported by laboratory tests - El Aal, Ahmed Abd; Abdullah, Gamil M. S.; Zakaly, Hesham M. H.; Awad, Hamdy A.; Omar, Ali E.; Sakr, Mohamed A. H.; Ene, Antoaneta (Frontiers in Environmental Science, 2023)
The current research study is aimed at studying the impact of sodium chloride on the performance of semi-arid soils in the Najran area of Saudi Arabia. Experimental work has been undertaken to investigate how adding salt to the semi-arid soil collected in the Najran area affects the boundaries of Atterberg, compaction characteristics, California bearing ratio, and shear strength. All testing was conducted on soil samples from different zones of the Najran area at varying depths of 1.5, 3, and 4.5 m along the soil profiles. The soil samples were analyzed individually and then compared with the same soil samples mixed with NaCl at different percentages of 5, 10, and 20% by weight of the dry soil. Using advanced techniques, such as the scanning electron microscope, energy dispersive x-ray analysis, and X-ray diffraction analysis, the stabilization process was examined. The findings revealed that NaCl significantly impacts the geotechnical characteristics of semi-arid soils. The maximum dry density increased from 1.995, 1.93, and 1.96 to 2.02, 1.99, and 2.03 g/cm3, and the optimal water content decreased from 9.47, 13.7, and 11.29 to 7.01, 9.58%, and 8.09% with 20% NaCl added at various depths, respectively. Shear resistance parameters were improved by adding 20% NaCl, where the soil cohesion increased from 0.1333, 0.0872, and 0.0533 to 0.1843, 0.1034, and 0.0372 kg/cm2, and the angle of internal friction increased from 24°, 25.5°, and 29° to 27.8°, 30°, and 33°, respectively. The liquid and plastic limits and, in turn, the plasticity index reduced as the added percentage of NaCl increased. Furthermore, the California bearing ratio percentages significantly increased and reached more than 50%. As a result, it is established that NaCl is an excellent stabilizer, especially at 20% concentration, and might be used as a sub-base substance in highway construction.